Exchange of core chromosomes and horizontal transfer of lineage‐specific chromosomes in Fusarium oxysporum. (21st April 2016) - Vlaardingerbroek, Ido; Beerens, Bas; Rose, Laura; Fokkens, Like; Cornelissen, Ben J. C.; Rep, Martijn
Summary: Horizontal transfer of supernumerary or lineage‐specific (LS) chromosomes has been described in a number of plant pathogenic filamentous fungi. So far it was not known whether transfer is restricted to chromosomes of certain size or properties, or whether 'core' chromosomes can also undergo horizontal transfer. We combined a directed and a non‐biased approach to determine whether such restrictions exist. Selection genes were integrated into the genome of a strain of Fusarium oxysporum pathogenic on tomato, either targeted to specific chromosomes by homologous recombination or integrated randomly into the genome. By testing these strains for transfer of the marker to another strain we could confirm transfer of a previously described mobile pathogenicity chromosome. Surprisingly, we also identified strains in which (parts of) core chromosomes were transferred. Whole genome sequencing revealed that this was accompanied by the loss of the homologous region from the recipient strain. Remarkably, transfer of the mobile pathogenicity chromosome always accompanied this exchange of core chromosomes.